Desenho de antena mecanicamente flexível para segmento "2 wheeler" multimedia - Mafalda Pereira Varela (2019)
As a consequence of the constant evolution of technology and in particular of communications technology, the need for the population to be permanently connected to each other has arisen. In view of these developments, it has also been important to add connectivity value in most electronic devices. In this way, the need of introducing this type of technology in the control panels of two-wheeler vehicles had increased, however, this should provide to the user a complete and safe experience. For this, it is intended to obtain as an end result an improvement of the current solution. That has a poor performance. This implementation either as a final result the use of the mobile phone through the control panel and connected to the helmets, which allows, for example, making phone calls or choosing music.In the current situation, chip antennas are used, chosen due to their easy implementation and small size. However they have a very low efficiency and therefore are not the ideal solution. Therefore, all over this dissertation, a different implementation will be studied and analyzed,using different solutions and always taking into account the space available, the cost of production and the implementation in the production line. This antenna should work for the Wi-Fi and Blue-tooth bands, so the center frequency will be 2.45GHz and the bandwidth will have to be between 2.4GHz and 2.5GHz. Throughout this work will be used CST for the design and simulation of the antenna and later prototyping and characterization in the anechoic chamber in order to confirm the results obtained in simulation.